2020
DOI: 10.1039/d0gc00052c
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pd/Ru metal supported graphene oxide nano-catalysts for hydrodeoxygenation (HDO) of vanillyl alcohol, vanillin and lignin

Abstract: Ru@GO and Pd/Ru@GO as hydrodeoxygenation (HDO) catalysts, forming p-creosol from vanillin, vanillyl alcohol and lignin after photo-catalytic fragmentation under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…It is generally believed that as the content of Pd 0 increases, the amount of metal active sites exposed on the catalyst surface increases, and the catalyst activity will gradually increase. [ 32,36 ] Remarkably, we observed that the defect degree and Pd 0 content on the surface of the catalyst exhibited similar trends with the MMP selectivity (Figure 4d). As shown in Figure 4d, the best catalytic activity was obtained over Pd/CAFR in 1 h at 50 °C.…”
Section: Catalytic Performance Of Catalystssupporting
confidence: 59%
“…It is generally believed that as the content of Pd 0 increases, the amount of metal active sites exposed on the catalyst surface increases, and the catalyst activity will gradually increase. [ 32,36 ] Remarkably, we observed that the defect degree and Pd 0 content on the surface of the catalyst exhibited similar trends with the MMP selectivity (Figure 4d). As shown in Figure 4d, the best catalytic activity was obtained over Pd/CAFR in 1 h at 50 °C.…”
Section: Catalytic Performance Of Catalystssupporting
confidence: 59%
“…5c). Compared to other metal catalysts previously reported, 13,16,[45][46][47][48][49][50][51] our present Ni 3 Co@NC@C catalyst exhibits a better or comparable catalytic performance in the aqueous phase HDO of vanillin (Table S1 †), and TOF values, even under mild reaction conditions.…”
Section: Paper Dalton Transactionsmentioning
confidence: 60%
“…The high number of oxygen-donor anchoring groups facilitates the immobilization and enhances the adsorption performance of metal catalysts [ 58 , 59 , 60 ]. Use of graphene oxide as a support has been reported in catalytic processes such as water or oxygen reduction reactions, coupling reactions, hydrodeoxygenation reactions, and, among other biomass conversion reactions [ 61 , 62 , 63 ]. Previous works have shown that the covalent grafting of {Mo 6 Br i 8 } 4+ cluster core complexes on the surface of GO sheets enhances the stability of the cluster active sites for catalytic reactions to afford good catalysts for hydrogen generation from water [ 36 ], carbon dioxide transformations into valuable chemicals [ 34 , 64 ], and degradation of organic pollutants [ 33 ].…”
Section: Introductionmentioning
confidence: 99%